Normalized difference vegetation index sensor-based nitrogen management in bread wheat (Triticum aestivum L.): Nutrient uptake, use efficiency, and partial nutrient balance - Mitra, Biplab; Singha, Prantick; Roy Chowdhury, Arnab; Sinha, Abhas Kumar; Skalicky, Milan; Brestic, Marian; Alamri, Saud; Hossain, Akbar (Frontiers in Plant Science, 2023)
The present experiment was conducted to assess the impact of fixed and variable doses (using a normalized difference vegetation index-sensor) of nitrogen (N) on wheat yields, nutrient uptake, nitrogen use efficiency, and soil nitrogen balance through the optimization of nitrogen dose. There were 10 treatments based on fixed and variable doses with different splits, and each treatment was replicated three times under a randomized complete block design. The treatments comprised fixed doses of 120 and 150 kg N ha–1 with different splits; variable doses based on sensor readings after application of 60, 90, and 120 kg N ha–1; 225 kg N ha–1 as a nitrogen-rich control; and no application of nitrogen as the absolute control. It was revealed that the application of a basal dose of 60 kg N ha–1 and another 60 kg N ha–1 at the crown root initiation stage followed by a sensor-guided N application significantly improved wheat grain yields and grain nitrogen uptake. However, straw nitrogen uptake was highest in N-rich plots where 225 kg N ha–1was applied. It was found that any curtailment in these doses at basal and crown root initiation stages followed by nitrogen application using a normalized difference vegetation index sensor later could not bring about higher crop yields. On average, wheat crops responded to 152–155 kg N ha–1 in both years of the study. Partial factor productivity along with agronomic and economic nitrogen use efficiency showed a declining trend with an increased rate of N application. Apparent N recovery values were comparable between normalized difference vegetation index sensor-based N application treatments and treatments receiving lesser N doses. Soil N status decreased in all the treatments except the nitrogen-rich strip, where there was a marginal increase in soil N status after the wheat crop harvest in the rotation. Partial nitrogen balance was negative for all the treatments except the control. From these 2-year field trials, it can be concluded that applying a normalized difference vegetation index sensor could be an essential tool for the rational management of fertilizer nitrogen in wheat grown in eastern sub-Himalayan plains.